The Effect of Accounting Information Systems and Work Environment on Employee Performance at the Department of Marine and Fisheries (DKP) of Central Sulawesi Province in Palu City - Ananda Aulia; Muliati; Tenripada; Mustamin (www.amertainstitute.com, 2025)
This study investigates the influence of the Accounting Information System (X1) and Work Environment (X2) on Employee Performance (Y) at the Marine and Fisheries Department of Central Sulawesi Province, located in Palu City, Indonesia. The research was motivated by the growing importance of reliable information systems and a conducive work environment in enhancing public sector performance. A total of 40 respondents were selected using purposive sampling from the department’s employee population. Primary data were collected through a structured survey instrument designed to measure the variables under study. The analytical method employed was multiple linear regression to determine the strength and significance of the relationships between the independent and dependent variables. The findings reveal that both the Accounting Information System and Work Environment have a positive and statistically significant effect on employee performance. The results suggest that improving technological infrastructure and organizational climate can lead to higher levels of productivity and effectiveness among civil servants. This study contributes to the body of knowledge on public sector management and highlights the need for continuous investment in information systems and human resource support mechanisms. The implications of these findings can serve as a reference for local government institutions in formulating strategies to enhance employee performance.